PROBLEMATIKA GURU DI SEKOLAH - Baharuddin, M. Sulton; Maunah, Binti (LPPM Institut Pendidikan Nusantara Global, 2022)
Abstrak P This study aims to determine the understanding of teacher problems, the kinds of problems experienced by teachers in schools and how to minimize these problems. The research method that the author uses is a qualitative approach with the type of library research (library research) with research data sources coming from various literatures, such as journals, books, personal documents, newspapers and so on. The results of the study can be concluded as follows: 1) Teacher problems are problems or problems experienced by teachers both when carrying out their duties in educating, teaching, and guiding students while at school. 2) Teacher problems are generally divided into two groups, namely internal problems that come from within the teacher and external problems that come from outside the teacher's personality. 3) The author provides several ways to minimize teacher problems that can be applied in schools, namely: Emphasizing Teacher Professionalism, Teacher Motivation and Implementing Continuing Professional Programs (PKB).